Translation, cross-cultural adaptation, and validation of the sino-nasal outcome test (SNOT)-22 for Georgian patients - Berdia Beridze; George Gogniashvili (Journal of Otolaryngology Advances, 2025)
Purpose The objective of this prospective case-control study was to perform translation, cross-cultural adaptation, and validation of the sino-nasal outcome test 22 (SNOT-22) into the Georgian language. Methods The translation and validation of the SNOT -22 questionnaire was performed using the forward-backward translation technique. After proper translation, the translated questionnaire was completed by chronic rhinosinusitis (CRS) patients before and after functional endoscopic sinus surgery (FESS) and by healthy individuals as controls. Results SNOT22 was translated into the Georgian language; the pilot study involved 34 patients, the test–retest group consisted of 30 patients with CRS and the control group of 71 patients without CRS complaints; 34 patients were evaluated before surgery and 3 months after surgery. The results showed a good internal correlation with Cronbach’s alpha - 0.88 at the initial examination, and 0.93 at the retest examination; both values suggest good internal consistency within SNOT-22. Pearson’s correlation coefficient was 0.72 (p<0.001), revealing a good correlation between initial scores and retest scores. Our sample of healthy individuals had a median score of 10,11 points and the instrument was able to differentiate between the healthy and the patient group, demonstrating its validity (p<0.0001). Conclusions The Georgian version of the SNOT-22 questionnaire is a valid outcome measure for patients with CRS.
Keywords: SNOT-22